1986
DOI: 10.1111/j.1432-1033.1986.tb09978.x
|View full text |Cite
|
Sign up to set email alerts
|

1H‐NMR study of mobility and conformational constraints within the proline‐rich N‐terminal of the LC1 alkali light chain of skeletal myosin

Abstract: Analysis by 'H-NMR spectroscopic techniques of the conformation of the N-terminal segment of the LC1 alkali light chain of rabbit skeletal muscle has shown that this portion of the molecule adopts a well-defined elongated configuration. T h s rod-like feature is a consequence of the Ala/Pro-rich composition and the functional aspects of such conformational preference in this and similar segments in other proteins are discussed.Studies of the dynamic aspects of protein structures have demonstrated the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Accordingly, the P1A1 sequence should exhibit a stronger PPII character since each Ala residue tends to assume the PPII conformation from the following Pro. Indeed, such a tendency was detected in NMR studies of the Pro‐rich N‐terminus of the light chain of skeletal myosin,53 which contains a (PA) 7 motif that exhibits an elongated conformation with the diffusion behavior of a rigid cylinder.…”
Section: Resultsmentioning
confidence: 93%
“…Accordingly, the P1A1 sequence should exhibit a stronger PPII character since each Ala residue tends to assume the PPII conformation from the following Pro. Indeed, such a tendency was detected in NMR studies of the Pro‐rich N‐terminus of the light chain of skeletal myosin,53 which contains a (PA) 7 motif that exhibits an elongated conformation with the diffusion behavior of a rigid cylinder.…”
Section: Resultsmentioning
confidence: 93%
“…In fact, one less alanine (from Ala199 of pB2) is present in the spectrum of the octomer compared to that of the trimer (Figs 7 and 5, respectively). NMR studies on myosin light chain [23], which also contains multiple Ala-Pro residues, concluded that these alternating amino acids result in a trans configuration for the proline, leading to a stiffened rod-like structure. Reduced flexibility of the N-terminal extension in pBl would decrease the likelihood of its resonances being resolved.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown by deletion mutagenesis studies that the site lies within the first 11 residues and that actin binding by these residues results directly in modulation of the kinetic properties of S1 (11). The remaining residues of the N-terminal extension of A1-type ELCs are highly proline-rich and form an extended structure (12) responsible for correctly positioning the actin binding site on the surface of actin (13). In this study we address the role of individual amino acids of the human atrial A1-type ELC (HmAtELC; Ref.…”
mentioning
confidence: 99%